0935 Association Between Chronotype, Sleep Duration, Weekend Catch-Up Sleep, and Depression Among Korean High School Students. (27th May 2020) - Yang, K; Jee Hyun, K; Hwangbo, Y; Koo, D; Kim, D; Sunwoo, J; Hong, S
Abstract: Introduction: The present study aimed to examine the association between chronotype, sleep duration, weekend catch-up sleep (CUS) duration, and depression among Korean high school students. Methods: A total of 8, 565 high school students who were analyzed from 15 nationwide districts in South Korea completed an online self-report questionnaire. Depressive mood was assessed using the Korean version of the Beck Depression Inventory. The following sleep characteristics were assessed: weekday and weekend sleep durations, weekend CUS duration, chronotype, perceived sufficiency of sleep, self-reported snoring and sleep apnea, daytime sleepiness, and sleep environment. Age, sex, body mass index, number of private classes, and proneness to internet addiction were also measured. Logistic regression analysis was conducted to compute odds ratios for the association between depression and sleep characteristics, after controlling for relevant covariates. Results: The prevalence of depression (BDI ≥ 16) was 1, 794 (20.9%). In the analyses of multivariate logistic regression, the late chronotype (odds ratio [OR], 1.71; 95% CI, 1.47-1.99), female (OR, 2.24; 95% CI, 1.99-2.53), underweight (OR, 1.27; 95% CI, 1.02-1.57) and obesity (OR, 1.41; 95% CI, 1.13-1.75), weekday sleep duration (OR, 0.86; 95% CI, 0.81-0.91), weekend CUS duration ≥ 2 hours (OR, 0.68; 95% CI, 0.55-0.85), ESS (OR, 1.08; 95% CI, 1.07-1.10), much (OR, 2.15; 95% CI, 1.63-2.84) and insufficient (OR, 1.71; 95% CI, 1.46-2.01) perceived sleep, snoring (OR, 1.27; 95% CI, 1.11-1.46) and witnessed apnea (OR, 2.10; 95% CI, 1.75-2.52), increased internet addiction (OR, 1.06; 95% CI, 1.05-1.06), high number of private education (OR, 0.76; 95% CI, 0.60-0.95), and poor sleep environment (OR, 1.86; 95% CI, 1.56-2.21) were associated with depression. Conclusion: Eveningness preference, insufficient weekday sleep duration, short weekend CUS duration, and self-reported snoring and sleep apnea were associated with an increased risk for depression. Support: